2004
DOI: 10.1518/hfes.46.1.1.30387
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electronic ANR and Conventional Hearing Protectors on Vehicle Backup Alarm Detection in Noise

Abstract: An experiment was conducted wherein masked thresholds (using ascending method of limits) for a backup alarm were obtained in pink and red noise at 85 and 100 dBA for 12 participants immersed in a probability monitoring task and wearing a conventional passive hearing protection device (HPD, an earmuff or a foam earplug), an active noise reduction (ANR) headset, or no HPD at all (only in 85 dBA noise). Results revealed statistically significant between-HPD differences in red noise (from 2.3 to 3.1 dB) and in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 9 publications
0
19
0
1
Order By: Relevance
“…[6,9] A single prior study actually examined, on a subjective basis, the effect of the backup alarm's acoustic features on how workers perform in localizing the source of the signal. In this study, Withington [8] used self-report measures to assess workers' performance in localizing conventional backup alarms as well as broadband ones.…”
Section: Introduction and Literature Backgroundmentioning
confidence: 99%
“…[6,9] A single prior study actually examined, on a subjective basis, the effect of the backup alarm's acoustic features on how workers perform in localizing the source of the signal. In this study, Withington [8] used self-report measures to assess workers' performance in localizing conventional backup alarms as well as broadband ones.…”
Section: Introduction and Literature Backgroundmentioning
confidence: 99%
“…[34][35][36][37] They can however reduce speech discrimination in background noise levels lower than 80 dBA, even in normal hearing listeners, [36][37][38][39] and particularly hinder sound detection [40] and speech perception [41] in individuals with hearing loss. For example, Robinson and Casali [40] showed that a tonal alarm could remain audible at fairly low SNRs (0 dB) in noise levels greater than 85 dBA when passive earmuffs are used, even in the presence of significant hearing loss (45-50 dB HL), indicating that workers with such hearing loss should hear the alarm if ISO 7731 [33] is met (alarm level exceeding that of the background noise by at least 15 dB).…”
Section: Comparative Studies On Detection and Audibilitymentioning
confidence: 99%
“…However, studies designed to simulate onthe-job listening conditions have reported poorer audibility with standard earplugs (Casali et al, 2004). As regards hearing impaired subjects, Abel et al (1982Abel et al ( , 1993 demonstrate that wearing earmuffs or earplugs deteriorates word recognition in noise when a high-frequency or flat sensorineural hearing loss is present.…”
Section: Introductionmentioning
confidence: 98%
“…To the authors' knowledge, only limited research has been published concerning communication with these protectors and the studies usually fail to establish univocally their benefits on signal perception in noise over standard passive protectors (Abel et al, 1993;Abel and Spencer, 1997;Casali et al, 2004;Dancer et al, 1999;Dolan and O'Loughlin, 2005).…”
Section: Introductionmentioning
confidence: 99%